Catalytic Ammonia Oxidation to Dinitrogen by Hydrogen Atom Abstraction. (11th June 2019) - Bhattacharya, Papri; Heiden, Zachariah M.; Chambers, Geoffrey M.; Johnson, Samantha I.; Bullock, R. Morris; Mock, Michael T.
Abstract: Catalysts for the oxidation of NH3 are critical for the utilization of NH3 as a large‐scale energy carrier. Molecular catalysts capable of oxidizing NH3 to N2 are rare. This report describes the use of [Cp*Ru(P t Bu 2 N Ph 2 )( 15 NH3 )][BAr F 4 ], (P t Bu 2 N Ph 2 =1, 5‐di(phenylaza)‐3, 7‐di(tert‐butylphospha)cyclooctane; Ar F =3, 5‐(CF3 )2 C6 H3 ), to catalytically oxidize NH3 to dinitrogen under ambient conditions. The cleavage of six N−H bonds and the formation of an N≡N bond was achieved by coupling H + and e − transfers as net hydrogen atom abstraction (HAA) steps using the 2, 4, 6‐tri‐ tert ‐butylphenoxyl radical ( t Bu3 ArO . ) as the H atom acceptor. Employing an excess of t Bu3 ArO . under 1 atm of NH3 gas at 23 °C resulted in up to ten turnovers. Nitrogen isotopic ( 15 N) labeling studies provide initial mechanistic information suggesting a monometallic pathway during the N⋅⋅⋅N bond‐forming step in the catalytic cycle. Abstract : Ein molekularer Ru‐Komplex oxidiert NH3 katalytisch zu Distickstoff unter Umgebungsbedingungen. Die Spaltung von sechs N‐H‐Bindungen und die Bildung einer N≡N‐Bindung wurde durch die Kopplung von Protonen‐ und Elektronentransfers unter Verwendung des 2, 4, 6‐Tri‐ tert ‐butylphenoxyl‐Radikals ( t Bu3 ArO . ) als H‐Atomakzeptor erreicht, resultierend in bis zu 10 katalytischen Umläufen.